EXPERIMENTAL STUDY ON REPLACEMENT OF BAGASSE ASH AS CEMENT AND QUARRY DUST AS SAND IN SELF -COMPACTING CONCRETE - T, Ganga; .N, Chandramohan (IJRDO - Journal of Mechanical And Civil Engineering, 2016)
Self-compacting concrete (SCC) is a flowing concrete mixture that is able to consolidate under its own weight. The highly fluid nature of SCC makes it suitable for placing in difficult conditions and in sections with congested reinforcement. But its initial higher supply cost over conventional concrete, has hindered its application to general construction. Therefore, for producing low cost SCC, it is prudent to look at the alternates to help reducing the SCC cost. This project aims at incorporating Bagasse Ash, which is a by-product from the sugar factor as a partial replacement material for cement to reduce the cost of cement and enhance the flow of SCC and sand was replaced by Quarry Dust, which is a by-product from the stone crushing factory. These two waste materials may bring the efficiency of the concrete to a considerable amount. The concrete mix proportions are varied for attaining the full characteristics of the SCC. The fresh and hardened concrete properties of various mixes of bagasse ash and quarry dust replacement mixes revealed that 7.5 percentage replacement of Bagasse ash and 40 percentage replacement of Quarry Dust yielded good workability and higher strength concrete than the control mix.